MINIMASI WASTE UNTUK PERBAIKAN PROSES PRODUKSI KANTONG KEMASAN DENGAN PENDEKATAN LEAN MANUFACTURING - Setiyawan, Danang Triagus; Soeparman, Sudjito; Soenoko, Rudy (JEMIS (Journal of Engineering & Management in Industrial System), 2013)
Packaging Factory have activities in  bag production. In order to increase the productivity, the company should manage the activities to increase valued added and decrease several waste. This study was purpose for analyzed the caused problems of waste, and give recommendation for minimizing the waste.  The problem solving at the study was using lean manufacturing concept approach.  The waste identification began with identification of  current state value stream mapping with weighting the waste in order to  understand the root of problem within production process.  The detail mapping selection was using Value Stream Analysis Tools (VALSAT).  Root Cause Analysis was used in order to understanding the root of problem for production process followed by FMEA for understanding the improving priority which has to be done. From the data analysis result, we found that the most dominant waste order is defect, waiting,  inventory, excessive transportation.The mapping detail used for analysis process as Process Activity Mapping Supply Chain Response Matrix and Quality Filter Mapping. From the result of study we found the decreasing of production time from 138.4 minute to 119.4 minute.  Decreasing lead time process could reach 13,7% comparing before the recovery step.